The influence of avoid game on children's knowledge about abduction prevention at TK ABA Danunegaran Yogyakarta - Nurpitasari, Mita; Pramudyani, Avanti Vera Risti; Sofyan, Iyan (Universitas Ahmad Dahlan, 2024)
Abduction is an event that has long-term impacts on its victims, such as trauma, stress, and confusion, and children are no exception. To prevent children from becoming victims again, an effective effort is to provide knowledge about abduction. The purpose of this study is to determine the effect of the AVOID game on children's knowledge about abduction prevention at TK ABA Danunegaran. The design used is a pre-test and post-test with a sample of 28 children. Furthermore, for data analysis techniques, the Wilcoxon test was used. The results showed that the Asymp. Sig. (2-tailed) value was 0.000 < 0.05, thus it can be concluded that there is a significant effect of the AVOID game on children's knowledge about abduction prevention. This study is limited to the number of samples and specific context, so further research is recommended to validate and test the long-term impact of the game on children's knowledge.